Anda di halaman 1dari 4

SECTION 2.

6 LIMITS AT INFINITY; HORIZONTAL ASYMPTOTES ❙❙❙❙ 1

|||| 2.6 Limits at Infinity; Horizontal Asymptotes

A Click here for answers. S Click here for solutions.


1–8 |||| Evaluate the limit and justify each step by indicating the 15. lim (sx 2  1  sx 2  1 )
xl
appropriate properties of limits.
1 5  2x 16. lim (s1  x  sx )
xl
1. lim 2. lim
xl x sx xl 3x
17. lim (s
3
1xs
3
x) 18. lim (sx 2  x  1  x)
xl x l 
x4 7t  4t
3
3. lim 4. lim
xl x 2  2x  5 tl 2t 3  t 2  3 19. lim ( x  sx ) 20. lim x 3  5x 2 


xl x l

1  x2  x 2x 2  1 x 1
7
5. lim 6. lim 21. lim 22. lim e x
2
x l  1  2x2  3x xl x  8x 2 xl x6  1 xl

1 sin 2x x3  1
7. lim 8. lim 23. lim x 2  x 4  24. lim
xl 3  sx xl x2 xl xl x4  1
■ ■ ■ ■ ■ ■ ■ ■ ■ ■ ■ ■

sx  3 x
25. lim 26. lim
9–26 |||| Find the limit. xl x3 xl sx  1
r4  r2  1 6t 2  5t
■ ■ ■ ■ ■ ■ ■ ■ ■ ■ ■ ■

9. lim 10. lim


rl r5  r3  r t l 1  t2t  3 27. Guess the value of the limit

s1  4x 2 sx 2  4x 5
11. lim 12. lim lim x 2 sin
xl 4x x l 4x  1 xl x2

1  sx by evaluating f x  x 2 sin5x 2  for x  1, 2, 3, 4, 5, 6, 7, 8,


13. lim 14. lim (sx 2  3x  1  x) 9, 10, 20, 50, and 100. Then confirm your guess by evaluating
xl 1  sx xl
this limit exactly.
2 ❙❙❙❙ SECTION 2.6 LIMITS AT INFINITY; HORIZONTAL ASYMPTOTES

|||| Answers
E Click here for exercises. S Click here for solutions.

2. 2
7 1 1
1. 0 3. 0 4. 2 5. 6 6. 2 7. 0
10. 3 12.  4 13. 1
1
8. 0 9. 0 11. 2
18.  2 19. 
3 1
14. 2 15. 0 16. 0 17. 0
20.  21.  22. 0 23.  24. 0 25. 0
26.  27. 5
SECTION 2.6 LIMITS AT INFINITY; HORIZONTAL ASYMPTOTES  3

Solutions

E Click here for exercises. A Click here for answers.

1 1  
√ = lim 3/2 = 0 by Theorem 5.  1/2 1 1/2
1. lim 2 2−
x→∞ x x x→∞ x 2x − 1 (11)  x2 
6. lim =  lim 
  x→∞ x + 8x2 x→∞ 1
5 5 +8
lim
+ 2 (5) x→∞ +2 x
5 + 2x x  
2. lim = lim x =  
lim 2 − lim 2
1 1/2  1/2
x→∞ 3 − x x→∞ 3 3
−1 lim −1 (5,1,2)  x→∞ x→∞ x  2−0
x x→∞ x =   =
1 0+8
lim + lim 8
1 x→∞ x x→∞
5 lim + lim 2 5 (0) + 2
(1,2,3) x→∞ x x→∞ 1
= = = by (9) and Theorem 5.
1 3 (0) − 1 2
3 lim − lim 1 √
x→∞ x x→∞
1 1/ x
= −2 by (9) and Theorem 5. 7. lim √ = lim √
x→∞ 3 + x x→∞ (3/ x ) + 1

1 4 √
+ 2 lim (1/ x ) 0
x+4 x x (5,1,3)
= x→∞
√ =
3. lim 2 = lim 3 lim (1/ x ) + lim 1 3 (0) + 1
x→∞ x − 2x + 5 x→∞ 2 5
1− + 2 x→∞ x→∞

 x x
= 0 by Theorem 5 with r = 12 .
1 4
lim + 2 1 1
(5) x→∞ x x Or: Note that 0 < √ < √ and use the Squeeze
=   3+ x x
2 5
lim 1 − + 2 Theorem.
x→∞ x x
1 1 sin2 x 1
lim + 4 lim 2 8. Since 0 ≤ sin2 x ≤ 1, we have 0 ≤ ≤ 2 for all
(1,2,3) x→∞ x x→∞ x x2 x
=  0. By (9) and Theorem 5 we have lim 0 = 0 and
x=
1 1
lim 1 − 2 lim + 5 lim 2 x→∞
x→∞ x→∞ x x→∞ x
1
0 + 4 (0) lim = 0. So, by the Squeeze Theorem,
x→∞ x2
= = 0 by (9) and Theorem 5.
1 − 2 (0) + 5 (0) sin2 x
lim = 0.
4 x→∞ x2
7t3 + 4t 7+ 2
4. lim = lim t 1 1 1
t→∞ 2t3 − t2 + 3 t→∞ 1 3 r4 − r2 + 1 − 3 + 5
2− + 3 9. lim 5 = lim r r r
t t r→∞ r + r3 − r r→∞ 1 1
1 1+ 2 − 4
lim 7 + 4 lim r r
(5,1,2,3)
=
t→∞ t→∞ t2 1 1 1
1 1 lim − lim 3 + lim 5
+ 3 lim 3
lim 2 − lim r→∞ r r→∞ r r→∞ r
t t→∞ t =
t→∞ t→∞ 1 1
7 + 4 (0) 7 lim 1 + lim 2 − lim 4
r→∞ r→∞ r r→∞ r
= = by (9) and Theorem 5.
2 − 0 + 3 (0) 2 0−0+0
   = =0
1 2 1+0−0
−1 +1
(1 − x) (2 + x) x x 6t2 + 5t 6t2 + 5t
5. lim = lim    10. lim = lim
x→−∞ (1 + 2x) (2 − 3x) x→−∞ 1 2 t→−∞ (1 − t) (2t − 3) t→−∞ −2t2 + 5t − 3
+2 −3
x x 6 + 5/t
   = lim
1 2 t→−∞ −2 + 5/t − 3/t2
lim −1 lim +1
x→−∞ x x→−∞ x lim 6 + 5 lim (1/t)
=    t→−∞ t→−∞
1 2 =
lim +2 lim −3 lim (−2) + 5 lim (1/t) − 3 lim (1/t2 )
x→−∞ x x→−∞ x t→−∞ t→−∞ t→−∞

(5,4,1,2,7) (0 − 1) (0 + 1) 1 6 + 5 (0)
= = = = −3
(0 + 2) (0 − 3) 6 −2 + 5 (0) − 3 (0)
√ √
1 + 4x2 (1/x2 ) + 4 0+4
11. lim = lim = =2
x→∞ 4+x x→∞ (4/x) + 1 0+1
4  SECTION 2.6 LIMITS AT INFINITY; HORIZONTAL ASYMPTOTES

√ √ √ 2
x2 + 4x − 1 + 4/x − 1+0 18. lim x +x+1+x
12. lim = lim = x→−∞
x→−∞ 4x + 1 x→−∞ 4 + 1/x 4+0 √ 2 
1 √ x +x+1−x
=− = lim x +x+1+x √
2
4 x→−∞ x2 + x + 1 − x
Note: In dividing numerator and denominator by x, we used x+1
√ = lim √ 2
the fact that for x < 0, x = − x2 . x→−∞ x +x+1−x
√ √ 1 + (1/x)
1− x (1/ x ) − 1 0−1 = lim
13. lim √ = lim √ = = −1 − 1 + (1/x) + (1/x2 ) − 1
x→−∞
x→∞ 1 + x x→∞ (1/ x ) + 1 0+1
1+0 1
= √ =−
√ − 1+0+0−1 2
14. lim x2 + 3x + 1 − x √ √
x→∞
√ 19. lim (x + x) = ∞ since x → ∞ and x → ∞.
√ 2 x2 + 3x + 1 + x x→∞
= lim x + 3x + 1 − x √ 2
x→∞ x + 3x + 1 + x 20. lim x3 − 5x2 = −∞ since x3 → −∞ and
x→−∞
x2 + 3x + 1 − x2 −5x2 → −∞ as x → −∞.
= lim √ 2
x→∞ x + 3x + 1 + x Or: lim x3 − 5x2 = lim x2 (x − 5) = −∞ since
3x + 1 x→−∞ x→−∞
= lim √ 2
x→∞ x + 3x + 1 + x x2 → ∞ and x − 5 → −∞.

3 + 1/x x7 − 1 1 − 1 x7
= lim 21. lim 6 = lim = ∞ since
x→∞ 1 + (3/x) + (1/x2 ) + 1 x→∞ x + 1 x→∞ (1/x) + (1/x7 )

3+0 3 1 1 1
=√ = 1 − 7 → 1 while + 7 → 0+ as x → ∞.
1+3·0+0+1 2 x x x
Or: Divide numerator and denominator by x6 instead of x7 .
√ √
15. lim x2 + 1 − x2 − 1 22. As x → ∞, x2 → ∞ and −x2 → −∞. Thus,
x→∞
√ √ 2
√ 2 √ x2 + 1 + x2 − 1 lim e−x = lim et = 0.
= lim x + 1 − x2 − 1 √ 2 √ x→∞ t→−∞
x→∞ x + 1 + x2 − 1
2 2 23. lim x2 − x4 = lim x2 1 − x2 = −∞ since x2 → ∞
x +1 − x −1 x→∞ x→∞
= lim √ √
x→∞ x2 + 1 + x2 − 1 and 1 − x2 → −∞.

2 x3 − 1 (1/x) − 1 x4 0−0
= lim √ 2 √ 24. lim = lim = =0
x→∞ x + 1 + x2 − 1 x→∞ x4 + 1 x→∞ 1 + (1/x4 ) 1+0
2/x √ √
= lim x+3 (1/ x ) + (3/x) 0+0
x→∞ 1 + (1/x ) + 1 − (1/x2 )
2 25. lim = lim = =0
x→∞ x + 3 x→∞ 1 + 3/x 1+0
0 √
=√ √ =0 x x/ x
1+0+ 1−0 26. lim √ = lim √ √
x→∞ x−1 x→∞ x − 1/ x
√ √ √
16. lim 1+x− x x
x→∞
= lim =∞
√ √  x→∞ 1 − 1/x
√ √ 1+x+ x √
= lim 1+x− x √ √ since x → ∞ and 1 − 1/x → 1.
x→∞ 1+x+ x √
Or: Divide numerator and denominator by x instead of x.
(1 + x) − x 1 
= lim √ √ = lim √ √
x→∞ 1 + x + x x→∞ 1 + x + x 27. If f (x) = x2 sin 5 x2 , then a calculator gives the
√ following approximate values: f (1) = −0.95892,
1/ x 0
= lim =√ =0
x→∞ (1/x) + 1 + 1 0+1+1 f (2) = 3.79594, f (3) = 4.74674, f (4) = 4.91902,
f (5) = 4.96673, f (6) = 4.98394, f (7) = 4.99133,

17. Using a3 − b3 = (a − b) a2 + ab + b2 with a = 3 1 + x f (8) = 4.99492, f (9) = 4.99683, f (10) = 4.99792,
√ f (20) = 4.99987, f (50) = 4.999997,
and b = 3 x, we have
√ √ f (100) = 4.9999998. It appears that
lim 3 1 + x − 3 x 
x→∞
lim x2 sin 5 x2 = 5.
(1 + x) − x x→∞
= lim 1
x→∞ (1 + x)2/3 + (1 + x)1/3 x1/3 + x2/3 Proof: Let t = . Then as x → ∞, t → 0 and
x2  
1
= lim =0 5 1 sin 5t
x→∞ (1 + x)2/3 + (1 + x)1/3 x1/3 + x2/3 lim x2 sin 2 = lim sin 5t = 5 lim = 5.
x→∞ x t→0 t t→0 5t